Critical Incident Technique in Teaching EFL Writing: A Study at One of Public Schools in Southeast Sulawesi - Abd Haris Takulani; Dewi Atikah; Diah Astuti (IAIN Kendari, 2021)
This study aims to quantitatively investigate the effect of Critical Incidents Technique on students’ writing aspects, particularly vocabulary, language use, and mechanics. The design of this research is pre-experimental one group pre-test and post-test design. The sample of this study was taken through purposive sampling based on the students’ writing score in EFL class. The students’ writing aspect was successfully improved through Critical Incident Technique (CIT) based on the writing score. This can be seen on the students’ mean score in three aspects of writing in pre-test was 48,39, while the students’ mean score in post-test was 81,50. There were 33,11 points differences between the students’ mean score in pre-test and post-test. This implies that students’ writing in content, organization, vocabulary, language use, and mechanic aspects can be improved using CIT. Although this research employs only quantitative design, it is recommended to have further investigation using qualitative study.